2021
DOI: 10.1021/acs.jpcc.1c04487
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Engineering of Inorganic Semiconductor VIS-Light-Driven Nanocatalysts: Experimental and Theoretical Understandings

Abstract: Photocatalytic performances of inorganic semiconductors are mainly restrained by two factors: their low solar light harvesting capabilities and fast recombination of the generated charge carriers. Concerning the first point, some visible (VIS) light-driven catalysts, such as WO3 and metal halide perovskites (MHPs), have emerged during the past years as promising alternatives to traditional TiO2 based materials. Hole/electron pairs recombination, on the other hand, can be somehow controlled and slowed down via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Several studies have reported that among various crystal structures of WO 3 , monoclinic (m-WO 3 ) (generated by annealing between 30 and 330 °C) is the most stable phase at room temperature. ,,,, Most often, exposed facets of (002) > (020) > (200) in the m-WO 3 with a distorted ReO 3 -type crystal structure result in rectangular sheet- and cubic-like nanoparticles. , Lin et al investigated the crystal facet effect of WO 3 nanowires and nanosheets in the photocatalytic oxidation of benzyl alcohol . They claimed that the WO 3 nanowires with the dominant exposed facet of {110} have a higher hole mobility than that of the WO 3 nanosheets with a {001} exposed facet, while the mobility of the electron on {110} is lower than that on {001}.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that among various crystal structures of WO 3 , monoclinic (m-WO 3 ) (generated by annealing between 30 and 330 °C) is the most stable phase at room temperature. ,,,, Most often, exposed facets of (002) > (020) > (200) in the m-WO 3 with a distorted ReO 3 -type crystal structure result in rectangular sheet- and cubic-like nanoparticles. , Lin et al investigated the crystal facet effect of WO 3 nanowires and nanosheets in the photocatalytic oxidation of benzyl alcohol . They claimed that the WO 3 nanowires with the dominant exposed facet of {110} have a higher hole mobility than that of the WO 3 nanosheets with a {001} exposed facet, while the mobility of the electron on {110} is lower than that on {001}.…”
Section: Introductionmentioning
confidence: 99%
“…Given these appealing advantages as a standalone or combined photocatalyst in various heterojunctions, WO 3 has been the subject of many experimental and theoretical studies in recent years. In particular, the solid/liquid interfacial properties, crucial for the efficiency of photocatalytic processes, have been theoretically investigated in the case of the WO 3 /water interface. ,, Previous computational studies have indeed addressed the fundamental understanding of the adsorption of water molecules on the γ-(001) surface [hereafter indicated as (001)]. ,,, Most of the reported studies have shown that water adsorbs preferentially in a molecular (undissociated) form since under-coordinated W atoms at the (001) surface are Lewis acids able to coordinate a water molecule …”
Section: Introductionmentioning
confidence: 99%
“…To this end, theory has been proved to be a valuable tool to shed light on the photophysical phenomena underlying the charge generation and recombination processes in semiconductor NPs, once realistic structural models and a reliable methodology are finely set up. , In a previous work, we developed a combined GW -density functional theory (DFT) protocol to get an estimation of the energetic levels of realistic WO 3 NPs within a GW level of accuracy . We employed this methodology to draw important design rules to tune the energetic alignment in single WO 3 NPs and in WO 3 /WO 3 and WO 3 /TiO 2 NP heterojunctions based on the morphological engineering of the NP structures.…”
Section: Introductionmentioning
confidence: 99%